Trafność procesu odpowiadania w polskiej adaptacji Skali Postrzeganej Siły Argumentu (PAS-PL): badanie pilotażowe - Kleka, Paweł; Szymański, Robert; Konat, Barbara (Człowiek i Społeczeństwo, 2026)
This article presents the translation and cross-cultural adaptation of the Polish version of the Perceived Argument Strength Scale (PAS-PL), along with a pilot study of response process validity in the context of arguments concerning COVID-19 vaccination. The adaptation followed international guidelines for the translation of psychometric instruments, using a bidirectional (forward–backward) translation procedure. Response processes were examined using the think-aloud method in a sample of ten students. Four categories of response problems were identified (confusion, disengagement, general response difficulties, and reactivity), and the reliability of protocol annotation was high (Krippendorff’s α = 0.808). In 83% of observations, no problems with interpretation or responding were detected. Exploratory analyses using a mixed-effects model indicated that problems occurred less frequently during the second administration of the questionnaire; a directionally consistent but statistically uncertain tendency was also observed for more frequent problems when selecting the midpoint response. The findings provide preliminary evidence for the response process validity of the PAS-PL and outline directions for further psychometric validation of the instrument.